A Novel Rotor Resistance Estimation Technique for Vector Controlled Induction Motor Drive Using TS Fuzzy - Saji Chacko; Chandrashekhar N.Bhende; Shailendra Jain; R.K. Nema (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
Induction motor with indirect field oriented control is well suited for high performance applications due to its excellent dynamic behavior. But, the indirect field oriented controller is sensitive to variations in rotor time constant, especially variation in rotor resistance. In this study a scheme based on the Rotor flux Model Reference Adaptive Controller is used for on line identification of the rotor resistance and thus improving the steady state performance of the drive.  The overriding feature of this estimation technique is the accurate identification of rotor resistance especially during transient and steady state conditions when the drive is operating at full load and at zero motor speed condition. Moroever, the effectiveness of the TS fuzzy controller utilizing rotor flux for online estimation of rotor resistance for four quadrant operation of motor drive is investigated and compared with the conventional PI and Mamdani fuzzy controller Simulation results in MATLAB/Simulink environment.have been presented  to confirm the effectiviness of the technique.